2005
DOI: 10.1016/j.ejvs.2004.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Ischaemic Preconditioning Protects Against Ischaemia/Reperfusion Injury: Emerging Concepts

Abstract: IP utilises endogenous mechanisms in skeletal muscle, liver, lung, kidney, intestine and brain in animal models to convey varying degrees of protection from I/R injury. To date there are few human studies, but recent reports suggest that human liver, lung and skeletal muscle acquire similar protection after IP. Specifically, preconditioned tissues exhibit reduced energy requirements, altered energy metabolism, better electrolyte homeostasis and genetic re-organisation, giving rise to the concept of 'ischaemia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(67 citation statements)
references
References 105 publications
1
62
0
4
Order By: Relevance
“…This protective effect is due to what has been designated I/R tolerance. (11) Since the results of various studies in those studies, IPC was performed using total hilar clamping. In a model of isolated perfusion, another group of authors (24) observed the effect of IPC on lung compliance and on gas exchange by stopping the perfusion (for 5 or 10 min) with or without simultaneous respiratory arrest.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This protective effect is due to what has been designated I/R tolerance. (11) Since the results of various studies in those studies, IPC was performed using total hilar clamping. In a model of isolated perfusion, another group of authors (24) observed the effect of IPC on lung compliance and on gas exchange by stopping the perfusion (for 5 or 10 min) with or without simultaneous respiratory arrest.…”
Section: Resultsmentioning
confidence: 99%
“…This appears to confer protection against later, longer ischemic episodes and the resulting reperfusion injury. This strategy has been studied in many organs and tissues, such as the heart, kidney, liver, intestine, brain, skeletal muscle and lung, (11) in animal models as well as in clinical studies. (12) In most lung studies, IPC was achieved through total hilar clamping, which does not correspond to the clinical reality of transplantation, in which the pulmonary artery is isolated for clamping separately from the other hilar structures.…”
Section: Introductionmentioning
confidence: 99%
“…Первоначально к защитному действию ИП от-носили только уменьшение размеров инфаркта, впоследствии оно было распространено на вос-становление в постишемическом периоде функ-циональной активности органов [66]. Уменьшение реперфузионных повреждений миокарда на фоне ишемического прекондиционирования еще называ-ют посткондиционированием [83]. Гипоксическое посткондиционирование по сути является новым способом реабилитации функционального состоя-ния органов (мозга, сердца) после тяжелых повреж-дающих воздействий гипоксического генеза.…”
Section: Aadsorasunclassified
“…There is an early ''classical'' period of protection occurring almost immediately after the ischaemic stimulus, followed by a ''late preconditioning'' phase, starting 12-42 hours later. 6 The exact mechanisms by which these adaptive changes are mediated remain unknown. Early preconditioning appears to be conducted through a pathway activated by a variety of substances released during ischaemia and reperfusion, such as adenosine, bradykinin, and opioids.…”
Section: Ischaemic Preconditioningmentioning
confidence: 99%